MENINGKATKAN KEMAMPUAN OPERASI PERKALIAN BAGI ANAK BERKESULITAAN BELAJAR KELAS IV MELALUI STRATEGI PEMBELAJARAN LANGSUNG - Resi Sringki (Universitas Negeri Padang, 2014)
Abtrak: This research was conducted based on the problem indicating low ability children in learn basic math, especially multiplication rows down. Therefore researchers provide intervention strategies with the help of direct interaction in order to help improve the operation of multiplication rows down. Purpose of this study is to prove a direct interaction strategy can improve the operation of multiplication for learning disabilities class IV of SD Negeri 17 Jawa Gadut Padang. This was quantitative research which used experimental method and Single Subject Research (SSR) form with A-B-A design. Data collection techniques used are tests or product permanent disfigurement are recorded in the format of data, the type size using a variable number of questions correct frequency is done by child. Based on the result of data analysis, it was revealed that the average score in the baseline session (A-1) was 0, in the intervention session was 7,54 and in the baseline (A-2) was 6,4. The tendency of tract in the baseline 2 phase (A-2) improved. The data overlapped in the baseline condition (A1) to the intervention condition (B) was 0%, and in the intervension (B) to the baseline 2 (A-2) was 18%. Based on these results, it was concluded that the use direct instruction can improve the operation of multiplication for learning disabilities class IV SD Negeri 17 Jawa Gadut Padang. The results of this research were expected to be taken into account by the teachers in using direct instruction strategies the students with learning disabilities in math. Kata Kunci : Learning disability; Operation of Multiplication Rows Down; Direct Intruction.